From Hardship to Hope: Someplace to Call Home as a Tool for Multilingual Learners - Ramirez, Darlene (WAESOL Educator, 2025)
This review examines the book Someplace to Call Home authored by Sandra Dallas offering a great example of modern literature that allows MLL teachers a vehicle for interesting classroom instruction. The book explores a historical fiction version of adversity during the Great Depression and Dust Bowl affording MLL students self-to-text connections and a historical overview of the US. Through this review, are educational standards which are insightful ways to engage students.